Comparative Analysis of Chrysanthemum Stunt Viroid Accumulation and Movement in Two Chrysanthemum (Chrysanthemum morifolium) Cultivars with Differential Susceptibility to the Viroid Infection - Nabeshima, Tomoyuki; Doi, Motoaki; Hosokawa, Munetaka (Frontiers in Plant Science, 2017)
Chrysanthemum stunt viroid (CSVd) was inoculated into two chrysanthemum (Chrysanthemum morifolium) cultivars, the CSVd-susceptible cultivar Piato and the CSVd-resistant cultivar Mari Kazaguruma. For CSVd inoculation, grafting and Agrobacterium-mediated inoculation were used. In grafting experiments, CSVd was detectable in Mari Kazaguruma after grafting onto infected Piato, but after removal of infected rootstocks, CSVd could not be detected in the uppermost leaves. In agroinfection experiments, CSVd systemic infection was observed in Piato but not in Mari Kazaguruma. However, agro-inoculated leaves of Mari Kazaguruma accumulated circular CSVd RNA to levels equivalent to those in Piato at 7 days post-inoculation. In situ detection of CSVd in inoculated leaves revealed that CSVd was absent in phloem of Mari Kazaguruma, while CSVd strongly localized to this site in Piato. We hypothesize that CSVd resistance in Mari Kazaguruma relates not to CSVd replication but to CSVd movement in leaves.